KONFLIK NELAYAN ( Studi Tentang Konflik Antara Nelayan Lokal dan Nelayan Pendatang di Kabupaten Sorong Selatan ) - , Alexander Duwit, SH., Prof.Dr.Purwo Santoso, MA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia is a multicultural country that is rich in culture and local wisdom, but at the same time has a double face. One hand, ethnicity is considered as a mosaic that characterized the birth of the nation-state primary where a growing pluralism presumed able to live and co-exist in a democracy. While the other hand, the process of assimilation and development is always followed by the turmoil and conflicts between tribes related problems and imbalances in the region, be it social, economic or political. This condition does not only take place at the national level, but also find significance in these areas. Thus the atmosphere reflected the conflict between local fishermen and the fishermen settlers in South Sorong has happened repeatedly. Attempts to meminimalir conflict ever initiated by a number of parties, but does not touch the root of the conflict. Therefore, this study was conducted to better track the dynamics of the conflict in South Sorong related to fishing communities. Local fishing economy is still traditional and subsystems, while the fishermen settlers have undergone modernization model of market economy. These differences lead to a gap between fishermen in the operational area, sparking the conflict. Data and facts to explain this conflict gained through observation, documentation and interviews with qualitative research methods. Cause of conflict is accumulated frustration, disappointment, and anger over the attitude and behavior of fishermen migrants deemed detrimental to the local fishermen. However, the roots of conflict in South Sorong fishermen actually related to the recognition of identity as a local fisherman, as the "natives" who claim the rightful owner of the economic resources of South Sorong. Smart solution is to resolve conflict transformation steps that lead to the recognition of identity, the following special rights that exist on the local fishermen through innovative assimilation effort to then make room for local fishermen in managing fisheries potential optimally. This study provides a framework for reconciliation and conflict resolution, and advocacy efforts through on the basis of "establishing policies favor affirmative (positive discrimination) on the local community which is the subject of advocacy to be able to find a point of compromise and negotiations with the fishermen settlers, so that local people and immigrants can work together or otherwise be able to compete fairly, both as a business in the fisheries sub-sector strategic business, (fuel distribution, capture, marketing and processing), as well as citizens are protected by the State.